Development and Standardization of Instant Food Mixes from Dehydrated Pumpkin and Pumpkin Seed Powder (Cucurbita moschata Duch ex Poir) - Dhiman, Anju K.; Negi, Vidya; Attri, Surekha; Ramachandran, Preethi (International Journal of Bio-resource and Stress Management, 2017)
Studies were carried out in the Department of Food Science and Technology, Dr. Y.S. Parmar University of Horticulture and Forestry, Nauni, Solan, Himachal Pradesh during the months of December 2013 to July 2014 for the development of instant food mixes (IMF) from dehydrated pumpkin and its seed flour. Dehydrated Pumpkin in the form of shreds, fine powder and granulated powder was used for the development of instant halwa mix, instant soup mix and instant porridge mix with better nutritional attributes. Instant halwa mix prepared using dehydrated pumpkin shreds and seed powder was found to be a good source of β-carotene (7.77 mg 100 g-1), fibre (2.91%) and protein (5.04%). While among all the instant halwa mixes prepared by using different forms of dehydrated pumpkin and its seed flour, ready-to-serve halwa prepared from granulated powder was much preferred by the panellist during sensory evaluation. Instant soup mix (ISM) developed by using pumpkin powder with various starch sources (rice starch, corn starch and potato starch), however, did not show much variation in chemical composition but ISM prepared with rice starch was most liked by the panellist. Instant porridge mixes prepared from broken wheat and pumpkin powder in the ratio of 60:40 was rated as the best by the panellist and was observed to contain highest β-carotene (7.37 mg 100 g-1) and fiber (1.21%). Henceforth, it is concluded that ripe pumpkin which otherwise is processed to limited extent, can be successfully utilized for the production of good quality and nutritionally enriched IMF.